2021
DOI: 10.4314/ahs.v21i.6s
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antiretroviral therapy interruptions and factors influencing return to care at the Nkolndongo Health District, Cameroon

Abstract: Background: Antiretroviral therapy is a lifelong commitment that requires consistent intake of tablets to optimize health outcomes, attain and maintain viral suppression. Objective: We aimed to elicit predictors of treatment interruption amongst PLHIV and identify motivating factors influ- encing return to care. Method: We conducted a cross-sectional study using a mixed-method approach in four hospitals in Yaoundé. Sociodemo- graphic and clinical data were collected from ART registers. Using purposeful samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The number of included disengaged participants per study ranged from 6 to 5008 people. Nine studies had quantitative surveys [12, 13, 15, 16, 19–21, 32, 33] (including studies where this was done alongside in‐depth interviews) and 14 studies included at least some information about how frequently various reasons were reported by participants [12–17, 19–24, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of included disengaged participants per study ranged from 6 to 5008 people. Nine studies had quantitative surveys [12, 13, 15, 16, 19–21, 32, 33] (including studies where this was done alongside in‐depth interviews) and 14 studies included at least some information about how frequently various reasons were reported by participants [12–17, 19–24, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 21 studies, three were conference abstracts [12][13][14] and the remainder were full papers (Table 1). Six studies were about general adult populations [12,[14][15][16][17][18], nine were about women who started ART while pregnant [19][20][21][22][23][24][25][26][27] and six were about various smaller populations (people who use drugs [13], indigenous people in an isolated area [28], adolescents [29], gay/bisexual/other men who have sex with men [30], men only [31] and women only [32]). No studies included children.…”
Section: R E S U Lt Smentioning
confidence: 99%